Abusing religion: literary persecution, sex scandals, and American minority religions - Goodwin, Megan (Rutgers University Press, 2020)
"Sex abuse happens in all communities, but American minority religions often face disproportionate allegations of sexual abuse. Why, in a country that consistently fails to acknowledge-much less address-the sexual abuse of women and children, do American religious outsiders so often face allegations of sexual misconduct? Why does the American public presume to know "what's really going on" in minority religious communities? Why are sex abuse allegations such an effective way to discredit people on America's religious margins? What makes Americans so willing, so eager to identify religion as the cause of sex abuse? Abusing Religion argues that sex abuse in minority religious communities is an American problem, not (merely) a religious one"--